United States Counterterrorism on ISIS - MINARDI, ANTON (Jurnal Studi Pemerintahan, 2016)
The U.S. counter terrorism on ISIS had implemented with various strategies including degrading ISISâ€™s capability, shaping global coalition to defeat ISIS, and using trained military armed men for Iraq army forces, Kurdi army, Arabian army, and moderate opposition groups to fight against Bassar. In early 2015, U.S. government described the group as â€œlosing this fightâ€ and reported that anti-ISIS operations had killed more than 8,500 fighters, destroyed hundreds of vehicles and heavy weapons systems, and significantly degraded IS command and control capabilities. Unfortunately, ISIS still exists with their weapons. Moreover, the fear against ISIS and the worst conditions it brings are not exclusive in Syria, Iraq and Libya as the conflict has already spread to many countries in Europe. These countries are in dilemma because despite being affected by the conflict, still they intend to give asylum to the refugees, but their concern is that with refugees coming in, there might be exporting of ISISâ€™s ideologies which leads to bigger and more serious concerns than the possibility of economic instability. Inevitably, there have been questions regarding the existence of ISIS today: How can groups such as ISIS still exists despite being attacked for 3 years by the U.S? The reality is that the U.S. initiated the establishment of new and democratic governments in Afghanistan, Iraq, and Libya few years ago bothers some experts on the continuing existence of ISIS.